Supervision of Mineral and Coal Mining Business Permits in Solok Regency - Andreono, Deni; Darnis, Darnis (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
This research is as follows: 1. To find out the supervision activities of the Mineral and Coal Mining Business Permits in Solok Regency. 2. To find out the obstacles that arose during the supervision of the Mineral and Coal Mining Business Permits in Solok Regency. The research method used is the empirical method (sociological juridical). After the data obtained is processed, the authors then analyze the data qualitatively. The results of this study In supervising the mining sector, the Provincial Government should be able to carry out these activities more than 1 time in 1 year considering that the mining sector is one of the important sectors both in the economic field and in its impact on the surroundingenvironment.